Beyond the method book: integrating movement, exploration, and improvisation into the elementary piano lesson - Szopinski, Sarah (Kansas State University, 2016)
Prominent elementary music methods like Orff-Schulwerk, Kodaly, Suzuki, Music Learning Theory, and Dalcroze Eurhythmics share a belief in a sound-before-symbol approach: delaying notation instruction in order to first develop audiation, musical vocabularies, and concrete musical experiences. Unfortunately, piano pedagogy has not taken the same journey, with method books continuing to center on reading from the earliest. While piano pedagogy has made great strides as a professional music community, now it must adopt the same sound-before symbol approach of its general music colleagues, making room for experiential and creative activities as a core component of instruction. Through the integration of movement, exploration, and improvisation activities like the included examples, teachers can move beyond strict adherence to the method book, and change their focus from notational literacy to authentic musicianship.
Keywords: Orff-Schulwerk; Piano pedagogy